Fitoestrógenos na cicatrização de feridas: revisão sistemática e estudo experimental com a Biochanina A - Neres, Wemerson de Santana (2025)
Wound healing can be impaired due to exacerbated inflammation and the consequent development of chronic wounds. In menopausal women, estrogen deficiency is a predisposing factor for this type of skin injury, while hormone replacement therapy may reverse the condition. Phytoestrogens are promising alternatives for wound healing because of their estrogen-like effects. However, the action mechanisms of these compounds in tissue repair remain poorly understood. Particularly for Biochanin A (BCA), whose healing effect in hypoestrogenic skin lesions is not yet well characterized. This study aimed to perform a systematic review emphasizing the wound healing mechanisms of phytoestrogens in preclinical models, as well as an experimental study of the effect of BCA in ovariectomized female mice. For the systematic review, searches were conducted in the LILACS, EMBASE, PUBMED, Scopus, and Web of Science databases, followed by study inclusion, data extraction, and analysis. To evaluate the healing effect of BCA, wounds inflicted on ovariectomized or sham-operated mice were topically treated with vehicle, BCA (0.03 mg, 0.09 mg, and 0.27 mg), or 17β-estradiol. On days 0, 3, 7, and/or 14, analyses were performed on wound size, myeloperoxidase activity, TNF-α, IL-1β, and IL-10 quantification, and histological assessment of lesions. Nineteen studies were included in the systematic review, with genistein being the most studied phytoestrogen. Phytoestrogens demonstrated healing, anti-inflammatory, antioxidant, reepithelializing, angiogenic, and fibroplastic effects. The main mechanisms of action identified were the classical estrogen receptor-mediated pathway and alternative pathways involving TNF-α/NF-κB, Nrf2, PI3K/AKT and ERK. In the experimental study, BCA reduced wound area during the inflammatory phase, as well as myeloperoxidase activity (neutrophil infiltration) and the pro-inflammatory cytokine TNF-α. It also increased levels of the anti-inflammatory cytokine IL-10 and promoted reepithelialization and collagen deposition in lesions. Phytoestrogens exhibit distinct mechanisms of action responsible for their effects on wound repair in preclinical models, either through estrogenic signaling or via independent pathways. BCA, in particular, demonstrated reparative effects on hypoestrogenic lesions, especially during the inflammatory phase, although further studies are needed to better explore its mechanisms in skin repair.